A systematic review and network meta-analysis of carbon dioxide provocation in psychiatric disorders. (November 2021) - Tural, Umit; Iosifescu, Dan V.
Abstract: Background: False suffocation alarm hypothesis has been widely used to explain carbon dioxide hypersensitivity in panic disorder (PD). However, hypersensitivity to carbon dioxide has been observed in other psychiatric disorders. We explored the specificity of carbon dioxide inhalation as a panic provocation test among psychiatric disorders via network meta-analysis. Methods: A systematic literature search on PubMed, EMBASE, and PsycNET was performed to acquire the studies using the carbon dioxide provocation test in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and checklists. Odds ratios (OR) for a panic attack (PA) induced by the carbon dioxide inhalation tests were extracted from each of the original studies and were pooled using the random-effects model. Results: Network meta-analysis on a pool of 2181 participants from 41 studies was used to compare the efficacy of carbon dioxide provocation tests among psychiatric disorders. The network meta-analysis showed that the odds for PA in response to carbon dioxide inhalation are higher in patients with PD, premenstrual dysphoric syndrome (PMDD), and social anxiety disorder (SAD) than healthy controls (HC). The odds for PA were not significantly different among patients with generalized anxiety disorder (GAD), obsessive-compulsive disorder (OCD), major depressive disorder (MDD), and healthy controls (HC). Conclusions: The vulnerability to the carbon dioxide provocation test is not limited to PD. The specificity of the test for PD is questionable, as individuals suffering from PMDD and SAD are also significantly more responsive to carbon dioxide inhalation compared to HC, OCD, MDD, and GAD. There may be shared underpinning biological mechanisms between PD, PMDD, and SAD.